Mobile Jawi courseware using serious game approach - Nur Syuhaida, Mohammad Roslan (2018)
Mobile Jawi Courseware using Serious Game Approach is an application designed for preschool students to master Jawi Language in effective and interesting way. The history of education in Malaysia shows that the Islamic Education has been taught either by using books or texts written in Jawi and still being practiced today. The drawback is students who are unable to master Jawi reading and writing skills will be left out in the Islamic subjects as Jawi is the medium of instruction of these subjects. This application will provide the learning module and also the mini games module. Students can learn Jawi character and also Jawi spelling through the learning module. The learning module can help them understand better and can memorize each character and also can help them master in Jawi spelling. While the mini games module is the platform for student to test their understanding and knowledge. There will be a few games provided for them to play and score will be given for each game. This application is a mobile based application for android platform. In order to develop this application, ADDIE methodology will be applied throughout the development from start to the end. The phase will be requirement analysis, system design, development, system implementation and lastly evaluation. Lastly, the expected outcomes from the application is children will be able to learn Jawi Language in an effective and attractive way. Besides, the element of serious game and fun learning can build children interest to learn and this application can be a good help for teachers to teach their students in future. This application also can be used by adult that have interest to start learning Jawi in the future.